Exploring the relationship between perceived social support and college students’ autonomous fitness behavior: Chain mediating effect test - Li, Na; Zhao, Shuqiang; Liu, Chanjuan; Dai, Kun; Huang, Wenjian (Frontiers in Psychology, 2023)
Objective This study aims to explore the effect of perceived social support on college students’ autonomous fitness behavior, and the mediating role of mental toughness and exercise self-efficacy. Methodology A survey participated by 985 college Students (average age, 19.55) was conducted by applying the following scales: The Perceived Social Support Scale, the Adolescent Self-Government Behavior Scale, the Mental Toughness Scale, and the Exercise Self-efficacy Scale (ESES). Results (1) Perceived social support can directly and positively predict autonomous fitness behavior, mental toughness, and exercise self-efficacy; mental toughness can directly and positively predict exercise self-efficacy. Likewise, perceived social support, mental toughness, and exercise self-efficacy can positively predict autonomous fitness behavior. (2) The indirect effect of the path with mental toughness as the mediating variable is 0.078, the indirect effect of the path with exercise self-efficacy as the mediating variable is 0.122, and the indirect effect of the path with mental toughness and exercise self-efficacy as the mediating variable is 0.082. (3) The total of all indirect effects is 0.282, and the effects of the three indirect pathways account for 18.25, 28.62, and 19.37% of the total, respectively. Conclusion The perceived social support can indirectly predict college students’ autonomous fitness behavior through the independent mediating effect of mental toughness and self-efficacy, as well as the chain mediating effect of the two. The claim that mental toughness and exercise self-efficacy perform a chain-mediate role in the positive effect brought by perceived social support on autonomous fitness behavior has been supported. This study revealed the relationship and mechanism between perceived social support and college students’ autonomous fitness behavior and further improved the research on the impact of perceived social support on college students’ autonomous fitness behavior.